The level of acceptance of ESSO autogas by private motorcar owners as perceived by ESSO autogas dealers / Abdul Hadi Abdul Ghani and Hasmawati Gani - Abdul Ghani, Abdul Hadi; Gani, Hasmawati (Faculty of Business and Management, 1984)
Esso autogas was introduced by Esso Malaysia Berhad barely a year ago. In general autogas or LPG used to power motor vehicle is something the public know little about it. The first autogas station was opened in June 8th, 1983. Until this study is made there are only (5) Esso autogas outlets which confines only in the Kelang Valley area. The main objective of this research was to determine the level of acceptance of Esso autogas by private motor car owners as percieved by Esso autogas dealers. In order to achieve the above objective it was decided that all the Esso autogas dealers in Kuala Lumpur and Petaling Jaya were personally interviewed. Other related informations from the Technical Division of the Road and Transport Department and the Ministry of Trade and Industry were also taken into consideration. The findings from the research showed that the level of acceptance of Esso autogas by private motor car owners as perceived by the Esso autogas dealers is very low. The findings also indicated that no incentive are given to those who wish to operate on LPG.